2011
DOI: 10.1007/s11606-011-1938-8
|View full text |Cite
|
Sign up to set email alerts
|

Updated Report on Comparative Effectiveness of ACE inhibitors, ARBs, and Direct Renin Inhibitors for Patients with Essential Hypertension: Much More Data, Little New Information

Abstract: OBJECTIVES:A 2007 systematic review compared angiotensin-converting enzyme (ACE) inhibitors and angiotensin II receptor blockers (ARBs) in patients with hypertension. Direct renin inhibitors (DRIs) have since been introduced, and significant new research has been published. We sought to update and expand the 2007 review. DATA SOURCES: We searched MEDLINE and EMBASE (through December 2010) and selected other sources for relevant English-language trials. STUDY ELIGIBILITY CRITERIA, PARTICIPANTS, AND INTERVENTION… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 114 publications
(247 reference statements)
0
35
0
2
Order By: Relevance
“…The role of aldosterone blockade through spironolactone, a mineralocorticoid antagonist, has potential benefit in some cases of resistant hypertension; the main adverse effect of spironolactone use is hyperkalemia [70]. Overall, little difference exists between the classes of ACEIs and ARBs in lowering BP and outcomes, with the exception of ADEs [71]; therefore, factors other than hypertension, such as ADEs, tolerability, and economic factors influence the choice of class. A Cochrane Hypertension Group Specialized Database in conjunction with other sources demonstrated little difference between ACEIs and ARBs regarding mortality and cardiovascular events; but good evidence suggested a lower incidence of withdrawal-related adverse effects for ARBs than for ACEIs.…”
Section: Angiotensin-converting Enzyme Inhibitors and Angiotensin Recmentioning
confidence: 99%
“…The role of aldosterone blockade through spironolactone, a mineralocorticoid antagonist, has potential benefit in some cases of resistant hypertension; the main adverse effect of spironolactone use is hyperkalemia [70]. Overall, little difference exists between the classes of ACEIs and ARBs in lowering BP and outcomes, with the exception of ADEs [71]; therefore, factors other than hypertension, such as ADEs, tolerability, and economic factors influence the choice of class. A Cochrane Hypertension Group Specialized Database in conjunction with other sources demonstrated little difference between ACEIs and ARBs regarding mortality and cardiovascular events; but good evidence suggested a lower incidence of withdrawal-related adverse effects for ARBs than for ACEIs.…”
Section: Angiotensin-converting Enzyme Inhibitors and Angiotensin Recmentioning
confidence: 99%
“…However, according to European Medicines Agency recommendations, aliskiren should not be prescribed to diabetic patients in combination with ACEi or ARBs [40]. The long-term, randomized, placebo-controlled morbidity/mortality trial ALTITUDE, which included 8,600 patients with type 2 diabetes, proteinuria, and a high cardiovascular risk already treated with an ACEi or ARB, was terminated in December 2011 due to an increased incidence of serious adverse events in the aliskiren 300 mg arm [15,16,17,40]. In this context, it is pertinent that chronic suppression of renin does not protect against the profibrotic influence of a chronically elevated urine flow.…”
Section: The Vasoconstrictive/pro-inflammatory Branchmentioning
confidence: 99%
“…Efficient RAS blockers at all these levels have been developed and are currently in use to block overactivation of RAS and to offer protection from RAS-related metabolic diseases including diabetes [8,9,10,11,12,13]. However, evidence of increased adverse effects from randomized clinical trials such as Aliskiren Trial in Type 2 Diabetes Using Cardio-Renal Endpoints (ALTITUDE) using double RAS blockade strongly advises against blocking RAS at multiple levels [14,15,16,17]. Furthermore, the Ongoing Telmisartan Alone and in Combination With Ramipril Global Endpoint Trial (ONTARGET) also demonstrated that dual RAS blockade was not beneficial compared to monotherapy with an ACE inhibitor (ACEi) or an AT1R blocker (ARB) in preventing serious outcomes in patients with known vascular disease or diabetes with end-organ damage [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…They inhibit the conversion of angiotensin I into angiotensin II and are expected to prevent cardiovascular, cerebrovascular, and renal complications associated with persistent high blood pressure as well as deterioration of heart failure [1, 2]. …”
Section: Introductionmentioning
confidence: 99%